Linking Teacher Instruction and Student Achievement in Mathematics: The Role of Teacher Language. Issue 3 (26th May 2016) - Grammer, Jennie K.; Coffman, Jennifer L.; Sidney, Pooja; Ornstein, Peter A.
Abstract : Although high-quality early educational environments are thought to be related to the growth of children's skills in mathematics, relatively little is known about specific aspects of classroom instruction that may promote these abilities. Data from a longitudinal investigation were used to investigate associations between teachers' language while teaching mathematics and their students' growth in mathematical skill during the 2nd grade. Specifically, the extent to which mathematics lessons included cognitive-processing language (CPL)—instruction that is rich in references to cognitive processes, metacognition, and requests for remembering—was related to changes in students' math achievement. Demonstrating the role of the language of instruction, the findings indicated that children whose 2nd-grade teachers included greater amounts of CPL during instruction evidenced greater growth in math fluency and calculation than did their peers whose teachers employed lower levels of CPL.